Inappropriate activity of local renin-angiotensin-aldosterone system during high salt intake: impact on the cardio-renal axis - Sabrina R. Gonsalez; Fernanda M. Ferrão; Alessandro M. Souza; Jennifer Lowe; Lucienne S. Lara (2018)
ABSTRACT Although there is a general agreement on the recommendation for reduced salt intake as a public health issue, the mechanism by which high salt intake triggers pathological effects on the cardio-renal axis is not completely understood. Emerging evidence indicates that the renin-angiotensin-aldosterone system (RAAS) is the main target of high Na+ intake. An inappropriate activation of tissue RAAS may lead to hypertension and organ damage. We reviewed the impact of high salt intake on the RAAS on the cardio-renal axis highlighting the molecular pathways that leads to injury effects. We also provide an assessment of recent observational studies related to the consequences of non-osmotically active Na+ accumulation, breaking the paradigm that high salt intake necessarily increases plasma Na+ concentration promoting water retention